Land use/land cover dynamics driven changes in woody species diversity and ecosystem services value in tropical rainforest frontier: A 20-year history. Issue 2 (February 2023) - Berhanu, Yericho; Dalle, Gemedo; Sintayehu, Dejene W.; Kelboro, Girma; Nigussie, Abebe
Abstract: Land use/land cover (LULC) change is a prominent problem in tropical forests. However, the fundamental question of how much woody species diversity was lost and ecosystem services value (ESV) changed in response to LULC conversion has rarely been studied. Therefore, the objective of this study was to assess the impact of LULC change on woody species diversity and ecosystem service value in the last two decades in the tropical rainforest frontier taking the case of Sheka Forest Biosphere Reserve (SFBR), Southwest Ethiopia. Supervised image classification with a maximum likelihood approach was employed and 90 quadrants were laid for the woody species inventory. Diversity indices and descriptive statistics were computed and the non-parametric test (Kruskal-Wallis) was used to test the effect of LULC change on woody species diversity. The benefit transfer method was used to estimate the monetary value of ecosystem services adopting coefficients from empirical studies. The woody species richness, diversity, and evenness varied (X 2  = 71.887, p < 0.05) across LULC types. The highest diversity was observed in the forest followed by cropland, coffee plantation, homegarden, and tea plantation. The estimated total ecosystem service value (ESV) was reduced by 21.56% from 309.11 million US$ in 1999 to 242.47 million US$ in 2020. Transition to mono-crop like tea plantations to maximize income not only altered native woody species but also induced the expansion of exotic species and reduced ESV, indicating a detrimental impact of LULC change on ecosystem integrity and stability in the future. Although LULC conversion destruct woody species diversity, cropland, coffee plantation and the homegardens were the refuge for some endemic and conservation priority species. Further, addressing contemporary challenges of LULC conversion through introducing mechanisms such as payment for ecosystem services that increase the economic and livelihood benefits of natural forests to local communities is important. Effective conservation and sustainable use approaches in which such species are systematically integrated into land use practices have to be planned and implemented. This could contribute to strengthening the conservation effectiveness of the SFBR of UNESCO and serve as a showcase for such conservation areas around the globe. The LULC challenges, particularly those emanating from local livelihood needs, could impede our efforts to conserve biodiversity, jeopardize the reliability of future projections, and have an impact on the conservation of threatened ecosystems, if it is not adequately addressed in time.